Proteins Play Important Role in Intercellular Adhesion Affecting on Fruit Textural Quality - Adhikari, Khem Bahadur; Shomer, Ilan (Journal of Food Science and Technology Nepal, 2014)
Fruit textural quality is becoming a major quality parameter for export, postharvest preservation, handling and processing. The main determinant of textural quality is intercellular adhesion (ICA) as attributed by the cell wall (CW) and its components. The importance of CW protein in ICA strengthening was exemplified in Medjoul date (Phoenix dactylifera L.) fruit, as a model. Fruit mesocarp sensitively responded to culture environment which was assayed in vitro at pH 3.5(< pKa) and pH 6.5(> pKa) in presence of organic acid molecules. The max penetration force, as a measure of ICA strength, of pH 3.5 (< pKa) incubated mesocarp ( 10.5 N) was signi cantly higher than that of pH 6.5 (> pKa) incubated fruits ( 2 N). The protein bands at 29 kDa, 75 kDa, 32 kDa and 87 kDa were exclusively or prominently found in ICA strengthened fruits (pH 3.5< pKa) compared to texturally injured fruits (pH 6.5 > pKa). DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10564 J. Food Sci. Technol. Nepal, Vol. 7 (31-35), 2012